Improving the Performance of Entrepreneurship Teachers in Implementing the Model of Factory Teaching - Imam Machfud (Faculty of Education Universitas Negeri Malang, 2020)
This study aims to improve the performance of entrepreneurship teachers through theimplementation factory teaching model at Vocational High School, SMKN 1 Blitar. It usedaction research approach through two cycles. Results of the two cycles indicates that there isan increase in test scores achieve by students. The finding confirms that the factory teachingwas able to support and improve learning process and performance of the entrepreneurshipteachers.